2013
DOI: 10.1128/iai.01149-12
|View full text |Cite
|
Sign up to set email alerts
|

Schistosome Egg Antigens Elicit a Proinflammatory Response by Trophoblast Cells of the Human Placenta

Abstract: f Schistosomiasis affects nearly 40 million women of reproductive age. Many of these women are infected while pregnant and lactating. Several studies have demonstrated transplacental trafficking of schistosome antigens; however, little is known regarding how these antigens affect the developing fetus and placenta. To evaluate the impact of schistosomiasis on trophoblasts of the human placenta, we isolated primary trophoblast cells from healthy placentas delivered at term. These trophoblasts were placed in cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 49 publications
2
13
0
Order By: Relevance
“…Our data are consistent with previous work from our laboratory regarding schistosome induced pro-inflammatory cytokine production across different models of trophoblast cells [19]. Outside of pregnancy, we and others have related these responses to nutritional, hepatic and hematologic morbidities in infected individuals [43][46].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our data are consistent with previous work from our laboratory regarding schistosome induced pro-inflammatory cytokine production across different models of trophoblast cells [19]. Outside of pregnancy, we and others have related these responses to nutritional, hepatic and hematologic morbidities in infected individuals [43][46].…”
Section: Discussionsupporting
confidence: 92%
“…Previously, we demonstrated that SEA can cause pro-inflammatory cytokine production in primary human trophoblast cells taken at term and allowed to syncytialize in vitro [19]. However, placentation is a dynamic process requiring trophoblast populations distinct in time and differentiation lineage to behave in specific and unique ways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 In vitro schistosome egg antigens can activate proinflammatory responses in trophoblasts. 37 Accordingly, the WHO now recommends praziquantel to women with schistosomiasis who are pregnant and lactating, 26 whereas a WHO informal consultation has further recommended that "women of childbearing age should not be excluded from population-based chemotherapy programmes for schistosomiasis." 38…”
Section: Female Genital Schistosomiasis: Africa's Most Common Chronicmentioning
confidence: 99%
“…Up to now, evidence of schistosome‐egg‐derived as well as filarial antigens in the cord blood, breastmilk and placentas of infected women and their newborns was provided by several studies . Further studies investigating possible effects of such transferred antigens have demonstrated firstly stimulatory effects on human trophoblast cells and placental inflammation leading to IL‐6, IL‐8 and MIP‐1alpha secretion, secondly that sensitization had occurred in terms of measurable antigen‐specific T‐cell responses in cord blood mononuclear cells (CBMCs) as well as activation of B cells and thirdly protection against reinfection . In general, maternal schistosomiasis leads to a more activated status of the innate as well as adaptive cell compartments of CBMCs, whereas filariasis during pregnancy seems to lead to tolerance with rather increased susceptibility of the offspring to develop filariasis during childhood indicating a certain longevity of the maternally imprint .…”
Section: Cytokine and Antigen Transfermentioning
confidence: 99%